Chemical Analysis of the Herbal Medicine Salviae miltiorrhizae Radix et Rhizoma (Danshen) - Hanqing Pang (Molecules, 2016)
Radix Salviae miltiorrhizae et Rhizoma, known as Danshen in China, is one of the most popular traditional Chinese medicines. Recently, there has been increasing scientific attention on Danshen for its remarkable bioactivities, such as promoting blood circulation, removing blood stasis, and clearing away heat. This review summarized the advances in chemical analysis of Danshen and its preparations since 2009. Representative established methods were reviewed, including spectroscopy, thin layer chromatography, gas chromatography, liquid chromatography (LC), liquid chromatography-mass spectrometry (LC-MS), capillary electrophoresis, electrochemistry, and bioanalysis. Especially the analysis of polysaccharides in Danshen was discussed for the first time. Some proposals were also put forward to benefit quality control of Danshen.